2009
DOI: 10.1007/s11144-009-5509-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the reaction of OH radicals with CH3OH and CD3OD studied by laser photolysis coupled to high repetition rate laser induced fluorescence

Abstract: A new experimental set-up coupling laser photolysis to a 10 kHz dye laser as the excitation source for OH fluorescence has been validated by measuring the rate constant of the reaction CH 3 OH + OH. The rate constant of the deuterated homologue CD 3 OD + OH has been measured under the same conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…The atmospheric degradation of CH 3 OH is governed by its reaction with OH radicals, and proceeds by abstraction of H ‐atoms from either the methyl or the hydroxyl site The rate coefficient shows a non‐Arrhenius behavior and increases at temperatures below 200 K because of enhanced stabilization of a pre‐reactive hydrogen‐bonded complex that can undergo tunneling . The rate coefficient at room temperature (298 K) has been measured many times and is recommended to be k 1 =9.0×10 −13 cm 3 s −1 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The atmospheric degradation of CH 3 OH is governed by its reaction with OH radicals, and proceeds by abstraction of H ‐atoms from either the methyl or the hydroxyl site The rate coefficient shows a non‐Arrhenius behavior and increases at temperatures below 200 K because of enhanced stabilization of a pre‐reactive hydrogen‐bonded complex that can undergo tunneling . The rate coefficient at room temperature (298 K) has been measured many times and is recommended to be k 1 =9.0×10 −13 cm 3 s −1 .…”
Section: Figurementioning
confidence: 99%
“…In this work, we have reinvestigated the influence of H 2 O on the rate coefficient of OH reaction with CH 3 OH using a direct method: laser photolysis coupled to a time‐resolved detection of OH radicals by laser induced fluorescence (LIF) after gas expansion (FAGE; fluorescence assay by gas expansion) . We have also repeated experiments using the same relative method as Jara‐Toro et al., and in addition to varying RH, we have also largely varied the gas volume in the Teflon bag to vary the surface to volume ratio.…”
Section: Figurementioning
confidence: 99%
“…[7][8][9] Thea tmospheric degradation of CH 3 OH is governed by its reaction with OH radicals,and proceeds by abstraction of H-atoms from either the methyl or the hydroxyl site [10] The rate coefficient shows an on-Arrhenius behavior and increases at temperatures below 200 Kb ecause of enhanced stabilization of apre-reactive hydrogen-bonded complex that can undergo tunneling. [10] Ther ate coefficient at room temperature (298 K) has been measured many times [11,12] and is recommended [13] to be k 1 = 9.0 10 À13 cm 3 s À1 .Very recently,Jara-Toro et al [14] reported that the reaction of OH with CH 3 OH is significantly catalyzed by water (enhanced by af actor of 2b etween 20 to 95 %o fr elative humidity), even at 294 K. Thes ame group also reported the water catalysis effect on reactions of OH with ethanol and npropanol. [15] Their results are based on awell-known relative method, where the consumption of the alcohol is measured relative to the consumption of areference compound (C 5 H 12 ) following their simultaneous reactions with OH radicals.T he reactions took place in a80liter Te flon bag, and OH radicals were generated continuously from the 254 nm photolysis of H 2 O 2 .T he ratio of the consumption of CH 3 OH versus the consumption of C 5 H 12 gives the ratio of the rate coefficients, k CH 3 OHþOH / k Ref+OH .This type of experiment was carried out at different relative humidities (RHs) of up to 95 %, and it was found that the ratio increased with increasing RH.…”
mentioning
confidence: 99%
“…[7][8][9] Thea tmospheric degradation of CH 3 OH is governed by its reaction with OH radicals,and proceeds by abstraction of H-atoms from either the methyl or the hydroxyl site [10] The rate coefficient shows an on-Arrhenius behavior and increases at temperatures below 200 Kb ecause of enhanced stabilization of apre-reactive hydrogen-bonded complex that can undergo tunneling. [10] Ther ate coefficient at room temperature (298 K) has been measured many times [11,12] and is recommended [13] to be k 1 = 9.0 10 À13 cm 3 s À1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation